Description of Knowledge and Dietary Patterns of Pregnant Women in Relation to The Incidence of Anemia - Rizty Emelia, Herizka; Noor Adha Aprilea; Nurun Nisa (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2025)
Anemia is a major health problem with widespread impacts on society, especially in developing countries like Indonesia. In Indonesia, the prevalence of anemia reaches 26% in children aged 5–12 years and 23% in adolescent girls aged 13–18 years. Southeast Asia is the region with the highest rate at 42%, while in developing countries the prevalence of anemia in pregnancy reaches 75%. Anemia in pregnancy carries the risk of complications for the fetus, the pregnant mother, and postpartum, and is often caused by iron deficiency in the body. Factors that influence hemoglobin levels in pregnant women include basic factors (knowledge, education, and socio-cultural factors) and direct factors (consumption of iron tablets, nutritional status, infection, and bleeding). Protein intake also plays an important role in iron transport, so its deficiency can increase the risk of anemia. This study aims to determine the overview of knowledge and consumption patterns of pregnant women regarding the incidence of anemia. The study was conducted in 2025 in Banjar Regency, South Kalimantan, with 30 pregnant women as respondents. The method used was a survey and interviews using a questionnaire and FFQ, with descriptive analysis. The independent variables were knowledge and consumption patterns, while the dependent variable was anemia. The results of the study showed that the highest frequency distribution of anemia categories for the knowledge variable was the sufficient category (46.7%), in the consumption pattern of Heme, Non-Heme and food ingredients that increase Fe, the most were in the frequent category (60.0%), the consumption pattern of food ingredients that inhibit Fe was the most in the rare category (53.3%). The conclusion of this study is that pregnant women in the Banjar Regency area regarding the occurrence of anemia in general have quite good knowledge and consumption patterns